Relationship Between Parental Support And Interest Entrepreneurship In Student In Smk Negeri 3 Kota Sungai Penuh - Luthfia, Fauzana; Yulastri, Asmar (Universitas Negeri Padang, 2023)
The research objectives were to describe: 1) the parental support in SMK Negeri 3 Kota Sungai Penuh, 2) the interest entrepreneurship in student in SMK Negeri 3 Kota Sungai Penuh, 3) analyze the relationship between parental support and interest entrepreneurship in student in smk negeri 3 kota Sungai Penuh. This type of research is quantitative with a correlational approach. The population in this study was all class XII students of all majors with a total of 194 people. The study sample amounted to 66 people with a sampling technique is Proportionate Random Sampling. Data collection techniques are carried out using questionnaires using the Likert scale which has been tested for validity and reliability. Data analysis uses descriptive analysis and correlational analysis. The results showed that: 1) Student parental support was in the excellent category (48%), 2) the level of student entrepreneurial interest was in the high category (51.5%), 3) Based on the results of the research analysis, a correlation value of rxy 0.556 and a calculated tcount(5.349) > ttable (1.997) . So it can be said that there is a positive and significant relationship between parental support and interest in entrepreneurship.